EFFECT OF SONICATION ON THE PROPERTIES OF COMPOSITE POLYPYRROLE/MICROCELLULOSE AND ITS POTENTIAL AS A CAPACITOR - Berlian Sitorus; Deni Pranata; Mariana Bara’allo Malino (Jurnal Kimia Riset, 2022)
The research aims to see the effect of sonication on the properties and capacitance of composites made of microcellulose isolated from Oil Palm Empty Fruit Bunches and Polypyrrole (PPy). PPy is a conductive polymer limited by its inflexibility; hence PPy is blended with microcellulose which can serve as a good matrix to increase the flexibility of PPy. The procedure to isolate the microcellulose was done by delignification, bleaching, and hydrolysis. In order to see the effect of sonication, hydrolysis was undertaken in two different ways : (i) without sonication and (ii) using sonication. Besides, the polymerization time for pyrrole was also varied: 4 and 16 hours and simultaneously composited with each microcellulose from (i) and (ii). The results show an increase in cellulose crystallinity from  35.6% without sonication to 40% after sonication, while the diameter of the sonicated microcellulose fibers tends to be smaller than the counterpart. The 4-hour polymerization time shows that the composite containing the unsonicated microcellulose has a higher capacitance than the composite with the sonicated microcellulose, 14.8 nF and 8.8 nF, respectively. Meanwhile, a similar capacitance is measured for the 16-hour polymerization, 1.90 nF and 2.68 nF, using the sonicated and un-sonicated microcellulose. Overall, although the capacitances of the composites are in the nanofarad scale, it can be said that the composite can be potentially used as a capacitor.